The Arabic language and the challenge of research and educational creativity in the knowledge society [اللغة العربية ورهان الإبداع البحثيّ والتعليمي في مجتمع المعرفة] - Rahmah Ahmad H. Osman; Adham Hamawiya Ali; Ahmad Ragheb Mahmoud; Muhammad Zamri Abdul Ghani (Penerbit Universiti Kebangsaan Malaysia, 2022)
Knowledge is an imperative measure of distinction across nations, as the greater the knowledge of a nation indicates its level of advancement and the development of its society. Research and educational innovations embraced by scientific institutions - especially universities - are the starting point for reaching a knowledge society. Along with the orientation towards a knowledge society at the beginning of the twenty-first century, the Arabic language has witnessed an exceptional demand, and learning it has become a top priority for many motives around the world. Accordingly, the quest towards an "enabled knowledge society" requires the use of a strong language that is capable of being the language of research and education. Hence, it is necessary to improve the Arabic language to be more open and innovative, according to its relationship with the worlds of knowledge. This can be achieved by strengthening educational training and scientific research and developing them after preparing mechanisms and synergizing efforts in order for the Arabic language to overcome the challenge of research and educational creativity in the knowledge society, and this is what this research attempts to explain.